Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.ppat.1003259
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-induced Activation of Latent HIV-1 Provirus in Actively Proliferating Primary T Lymphocytes

Abstract: HIV-1 latency remains a formidable barrier towards virus eradication as therapeutic attempts to purge these reservoirs are so far unsuccessful. The pool of transcriptionally silent proviruses is established early in infection and persists for a lifetime, even when viral loads are suppressed below detection levels using anti-retroviral therapy. Upon therapy interruption the reservoir can re-establish systemic infection. Different cellular reservoirs that harbor latent provirus have been described. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 66 publications
(61 reference statements)
2
53
1
Order By: Relevance
“…However, increasing concentrations of ICOSL-blocking antibodies did not reverse latency (data not shown), despite ICOSL expression by MDDCs (110). Of note, ICAM1, upregulated by TNF signaling on DCs, was recently associated with HIV reactivation in proliferating CD4 ϩ T cells, in a similar system (111). Since Jurkat cells do not multimerize LFA-1, which is crucial for its activation and interaction with ICAM1, we did not challenge this axis (112).…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing concentrations of ICOSL-blocking antibodies did not reverse latency (data not shown), despite ICOSL expression by MDDCs (110). Of note, ICAM1, upregulated by TNF signaling on DCs, was recently associated with HIV reactivation in proliferating CD4 ϩ T cells, in a similar system (111). Since Jurkat cells do not multimerize LFA-1, which is crucial for its activation and interaction with ICAM1, we did not challenge this axis (112).…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells, such as DC, are non-permissive for HIV-1, and the rate of infection is very low [22]. Studies of HIV-1 latency in DC are hindered by the difficulties associated with effectively developing replicative infection in DC, and the absence of models or cell lines for DC reservoirs [23]. To investigate the role of DC-SIGN-induced signaling pathways in HIV-1 provirus reactivation, we generated cell models of HIV-1 DC reservoirs using 293T cells transfected with a DC-SIGN expression plasmid and HIV-1 5′LTR reporters and CEMBru cells transfected with a DC-SIGN expression plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…The higher levels of IFN-γ activity (represented by higher levels of plasma neopterin) induced by malaria also indicated immune system and T cell activation [13]. The higher levels of neopterin induced by malaria especially indicated the activation of macrophages [36], which may be more critical in the process of SIV reservoir purging because Van der Sluis et al have shown that APCs such as myeloid dendritic cells can activate latent T cells more than other T cell activators do [37]. A correlation analysis of plasma neopterin and the activation level of CD4+ T cells might also have uncovered this phenomenon (Additional file 2: Figure S2D).…”
Section: Discussionmentioning
confidence: 99%